The effect of nursing intervention based on Autar scale results to reduce deep venous thrombosis incidence in orthopaedic surgery patients - Hui-Zhen Yin; Ci-Ming Shan (Elsevier, 2015)
Purpose: To reduce the incidence of deep venous thrombosis (DVT) with nursing intervention based on the Autar DVT risk assessment scale among orthopaedic surgery patients. Methods: We recruited 216 orthopaedic surgery patients at our hospital between September 2013 and March 2014. The patients were assigned to intervention and historical control groups based on the time of admission. Using the Autar DVT risk assessment scale, we assessed the DVT risk levels in both groups; the intervention group received the corresponding prophylactic measures while the control group received routine nursing. Results: The DVT incidence rate and the D-dimer level on postoperative day 3 in the intervention group were lower (1.82%; 623 ± 225 μg/L, respectively) than that of the control group (9.43%; 825 ± 201 μg/L, respectively); both differences were statistically significant (p < 0.05). Conclusions: The Autar scale is beneficial when used in orthopaedic surgery patients; corresponding nursing intervention based on Autar scale assessment can prevent DVT effectively.